Profile of Subjective Complaints and Activities of Daily Living among Current Patients with Minamata Disease after 3 Decades - Kinjo, Y.; Higashi, H.; Nakano, A.; Sakamoto, M.; Sakai, R. (Environmental research, 1993)
We surveyed 1144 current patients with Minamata disease (MD) aged 40 or over in the Minamata area and the same number of neighbor controls matched with age and sex by questionnaire interview with regard to subjective complaints and activities of daily living (ADL). From analysis of subjective complaints, it was found that MD patients had significantly higher rates of all complaints than controls (P < 0.05). Multivariate analysis showed that subjective complaints in controls were clearly separated into the following two categories: sensory disturbances and movement nerve disturbances, but all complaints in MD patients formed one cluster. Such variation seemed to be due to methylmercury exposure to the central nervous system. ADL analysis revealed that the difference in the ADL disability between MD patients and controls significantly increased with age (P < 0.05) and that ADL disability in MD patients was aggravated by aging.